PARENTING PENDIDIKAN SEKS SEBAGAI UPAYA PENCEGAHAN SEXUAL ABUSE PADA ANAK USIA DINI DI INDONESIA: SEX EDUCATION PARENTING AS AN EFFORT TO PREVENT SEXUAL ABUSE IN EARLY CHILDHOOD IN INDONESIA - Audini, Elma; Quthny, Abu Yazid Adnan; Kiromi, Ivonne Hafidlatil (Thufuli, 2023)
Recent years have seen an increase in incidents of sexual violence related to early childhood in Indonesia. Based on the latest data from the Ministry of Women's Empowerment and Child Protection for 2022 starting from January 2022 to September 2022, there were cases of violence against a total of 15,759 female victims followed by 2,729 male victims. Sex education is still something that is considered taboo by the majority of Indonesian people, they view educating children about sexuality as a bad thing because they believe that sex education only consists of training children in negative things without any educational component. Of the many cases of sexual abuse in early childhood that are increasingly sticking out to the public and this phenomenon the researcher is interested in carrying out a deepening of the importance of sex education for early childhood through the design of a qualitative narrative method by carrying out a literature review, where the author examines various data sources along with information from various sources related to the issues set. The first and foremost line of defense against the sexual abuse of children is their parents. Parenting is an attempt by parents to behave towards their children as parents should. By implementing Good Parenting Communication Skills, this parenting movement is needed because parents must understand the risks and know how to prevent sexual violence in children responsively and effectively. Sex education for children with a daily activity approach, while learning about sexuality with daily activities. Such as potty training/toilet training, not showing private body parts, naming private body parts with the correct biological names.